Exploit your comparative advantages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
An economist from Zambia?s National Farmers Union suggests that farmers need to be very careful in choosing which crops to grow, so that these match the capabilities of their land and climate, and the type of markets which they can access.